Symbolic distance affects two processing loci in the number comparison task. - Oriet, Chris; Tombu, Michael; Jolicœur, Pierre (Memory & Cognition, 2005)
A dual-task procedure was used to investigate the attentional requirements of number processing. The results show that (1) numeric information in Task 2 can be retrieved in parallel with capacity-demanding processing in Task 1 but (2) comparing two quantities requires central capacity, which is depleted by switching from one task to another. This finding resolves an apparent discrepancy in the literature, in which digit magnitude information has not been retrieved in parallel with a second task (Logan & Schulkind, 2000), despite repeated demonstrations that this information is retrieved autonomously, even when it is deleterious to performance (Henik & Tzelgov, 1982). A model is proposed to reconcile existing findings with the new ones revealed in the present investigation. Reprinted by permission of the publisher.